IL-4 induced MUC4 enhancement in respiratory epithelial cells in vitro is mediated through JAK-3 selective signaling - Sachdev Goverdhan P (Respiratory Research, 2006)
Abstract Background Recent studies have identified MUC4 mucin as a ligand for activation of ErbB2, a receptor tyrosine kinase that modulates epithelial cell proliferation following epithelial damage in airways of asthmatics. In this study, we investigated the potential role of IL-4, one of the Th2 inflammatory cytokines persistent in asthmatic airways, in regulating MUC4 expression using a cell line NCI-H650. Methods Real time PCR analysis was performed to determine concentration and time dependent effects of IL-4 upon MUC4 expression. Nuclear run on experiments were carried out to explore potential transcriptional modulation. Western blotting experiments using a monoclonal antibody specific to ASGP-2 domain of MUC4 were performed to analyze MUC4 glycoprotein levels in plasma membrane fractions. To analyze potential signal transduction cascades, IL-4 treated confluent cultures were co-incubated, separately with a pan-JAK inhibitor, a JAK-3 selective inhibitor or a MEK-1, 2 (MAPK) inhibitor at various concentrations before MUC4 transcript analysis. Corresponding transcription factor activation was tested by western blotting using a monoclonal p-STAT-6 antibody. Results MUC4 levels increased in a concentration and time specific fashion reaching peak expression at 2.5 ng/ml and 8 h. Nuclear run on experiments revealed transcriptional enhancement. Corresponding increases in MUC4 glycoprotein levels were observed in plasma membrane fractions. Pan-JAK inhibitor revealed marked reduction in IL-4 stimulated MUC4 levels and JAK3 selective inhibitor down-regulated MUC4 mRNA expression in a concentration-dependent fashion. In accordance with the above observations, STAT-6 activation was detected within 5 minutes of IL-4 stimulus. No effect in MUC4 levels was observed on using a MAPK inhibitor. Conclusion These observations signify a potential role for IL-4 in MUC4 up-regulation in airway epithelia.